18=6f-2(f+3)

Simple and best practice solution for 18=6f-2(f+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18=6f-2(f+3) equation:


Simplifying
18 = 6f + -2(f + 3)

Reorder the terms:
18 = 6f + -2(3 + f)
18 = 6f + (3 * -2 + f * -2)
18 = 6f + (-6 + -2f)

Reorder the terms:
18 = -6 + 6f + -2f

Combine like terms: 6f + -2f = 4f
18 = -6 + 4f

Solving
18 = -6 + 4f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-4f' to each side of the equation.
18 + -4f = -6 + 4f + -4f

Combine like terms: 4f + -4f = 0
18 + -4f = -6 + 0
18 + -4f = -6

Add '-18' to each side of the equation.
18 + -18 + -4f = -6 + -18

Combine like terms: 18 + -18 = 0
0 + -4f = -6 + -18
-4f = -6 + -18

Combine like terms: -6 + -18 = -24
-4f = -24

Divide each side by '-4'.
f = 6

Simplifying
f = 6

See similar equations:

| 5x-7=11-2x | | 8=8x-5 | | 7.5x=15.0 | | 8[k+20]=52 | | 3y+3x=15 | | .4x+1.18=3.1(2-.01x) | | 5w^2-20=0 | | -7.5=15.0 | | 5.5= | | 5(2-1)+x+17=5x+6(x+2) | | -4n-11=4n+21 | | 2b^2=8b-6 | | .3x-2.1=1.5x+2.3 | | v^4-5v+4=0 | | (x+6)-(2x+7)=-9 | | 3(x+1)=2(x+1)+2x | | -7+x=-3 | | 3(4x+2)=5x+2 | | 12.5=2g-g-3.5 | | 9x^2-z=0 | | z+11.7=-7.1 | | 9=6x-4 | | 3/8=2/3-5x/6 | | -5.1+b=7.1 | | z+11.7=7.1 | | 7t+3=5t-11 | | 3[2t+4]=42 | | 2x-6x=42 | | .5x-2.3=3.1x+1.9 | | 64a^2-81=0 | | 4(5x+1)=5x-8x | | 15q=q-25q |

Equations solver categories